Peter finkbeiner's Asia (Time, 1996)
Peter Finkbeiner, who grew up in the post-war rubble of Berlin, developed a wanderlust at an early age. His child-star career (in theatre, television and film) had carried him all over Europe before his academic one took him to three continents. A journalist-photographer-publisher of international magazines and author of city guides and travel books – from The Grand Hotels of Europe to The Islands of the South Seas – Finkbeiner became famous as the creator of the IN World Guide, the esoteric almanac of the most important, beautiful and social places on earth – and the world’s most exclusive and expensive pocketbook. Acclaimed by the world press as “The Beautiful-Life Bible for the Chosen Few” (Esquire), the IN World Guide remains the only guide to the entire world in a single volume.